Further improvements in sorting grids for the crustacean trawl fishery off the Southern coast of Portugal - Millar, Russell B. (2020)
Bottom-trawl fishing for crustaceans off the Portuguese south and southwest coasts is a very important segment of the Portuguese fishing fleet, where annual rates of discarding have ranged from approximately 38% to as much as 70% of the total catch. Past experiments to address this problem encompassed the testing of different codend mesh sizes and configurations, square mesh windows and rigid grids to enhance species and size-selectivity. While the use of a Nordmore grid has proved quite efficient in separating out blue whiting (Micromesistius poutassou), it also led to some losses of the two main crustacean target species, Norway lobster (Nephrops norvegicus) and rose shrimp (Parapenaeus longirostris). The present study addresses that limitation by using a modified grid with 20 mm bar spacing and two open sections, designed with the purpose of separating fish and crustacean species into upper and lower codends. Good separation was achieved, with about 80% of the blue whiting (in number) directed towards the upper trawl section and caught in the upper codend, while a similar percentage of Norway lobster was caught in the lower codend. The grid bars had 50% retention for Norway lobster at 34.1 mm carapace length. The results herein will enable this gear configuration to be finetuned with regard to codend mesh sizes and bar spacing, so as to optimize both retention of Norway lobster and exclusion of blue whiting. For example, compared to using the minimum 70 mm diamond mesh size, using an 80 nun diamond mesh upper codend would reduce Norway lobster catch weight by just 1.6% but reduce the number of blue whiting caught by 42%.